Stochastic Resource Allocation for Uplink Wireless Multi-Cell Ofdma Networks - Adasme-Soto, P (Springer Verlag, 2014)
In this paper, we propose a (0-1) stochastic resource allocation model for uplink wireless multi-cell OFDMA Networks. The model maximizes the total signal to interference noise ratio produced in a multi-cell OFDMA network subject to user power and subcarrier assignment constraints. We transform the proposed stochastic model into a deterministic equivalent binary nonlinear optimization problem having quadratic terms and second order conic constraints. Subsequently, we use the deterministic model to derive an equivalent mixed integer linear programming formulation. Since the problem is NP-Hard, we propose a simple reduced variable neighborhood search (VNS for short) metaheuristic procedure [6,7]. Our preliminary numerical results indicate that VNS provides near optimal solutions for small and medium size instances when compared to the optimal solution of the problem. Moreover, it provides better feasible solutions than CPLEX when the instances dimensions increase. Finally, these results are obtained at a significantly less computational cost. © 2014 Springer International Publishing.
Keywords: mixed integer linear programming; resource allocation; variable neighborhood search; Wireless multi-cell OFDMA networks